Analisis Kasus Pelanggaran Hak Cipta Lagu “Helo Kuala Lumpur” Terhadap Lagu “Halo-Halo Bandung” Beserta Penyelesaian Sengketanya - Balqis Zhafirah Febriana (Lembaga Pengembangan Kinerja Dosen, 2024)
The advancement and development of technology and information will certainly have an impact on the creative industry, including music, which undoubtedly has a copyright. This copyright must be protected and enforced by appropriate laws considering the increasing risk of copyright infringement. For example, the copyright infringement case by the song